Should We Consider Mutation Analysis in Evaluating the Prolonged Jaundice of Newborn Infants? - Young Don Kim (Korean Society of Neonatology, 2024)
Purpose Uridine diphosphate glucuronosyltransferase 1A isoform 1 (UGT1A1) is a crucial enzyme in bilirubin metabolism. Mutations in this gene cause prolonged unconjugated hyperbilirubinemia in infants. This study aimed to investigate the prevalence of UGT1A1 mutations and their association with prolonged, unexplained, and unconjugated hyperbilirubinemia in infants. Methods From July 2019 to March 2023, 74 infants with prolonged jaundice lasting >21 days were enrolled in this study. Diagnostic evaluations, including UGT1A1 mutation analysis, were performed to identify the underlying causes of hyperbilirubinemia. This retrospective review evaluated the incidence and types of mutations in UGT1A1. The clinical and laboratory findings were compared based on the specific mutations detected. Results Thirty-three infants agreed to UGT1A1 mutation analysis, and 30 (90.9%) were positive for UGT1A1 mutations. Single-nucleotide variants were detected in 20 (66. %) infants. The remaining 10 (33.3%) infants had multiple variants. No significant demographic differences were observed between the group that underwent UGT1A1 mutation analysis and the group that did not. Among the identified genetic variants, c.211G>A (46.5%) and c.-3275T>G (30.2%) were the two most common variants. The other variants had the following percentages: c.1456T>G, c.-64G>C, and c.1091C>T (4.7% each); and c.-3152G>A, c.189C>T, and c.-41.-40 dup (2.3% each). Among the 20 infants with the c.211G>A variant, eight (40.0%) had a homozygous genotype and 12 (60.0%) had a heterozygous genotype. Infants harboring other variants exhibited heterozygous genotypes. When comparing the group with confirmed UGT1A1 mutations to the group without detected mutations, breastfeeding was the only significant factor (p=0.027). No significant differences were found between the group with singlenucleotide variants and the group with multiple genetic variants or between the homozygous genotype group with c.211G>A and the heterozygous genotype group. Conclusion Neonates with prolonged unconjugated hyperbilirubinemia may have a higher chance of UGT1A1 mutation than expected. Analysis of UGT1A1 mutations may be beneficial in infants with prolonged unexplained jaundice.